Implementation of Life Skills Based Education in Public High School 1 Jangka Buya, Pidie Jaya Regency, Aceh Province - Syahril B, Alfi; Rahmi Novalita, Rahmi Novalita; Fitrah, Hariki (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The aim of this research is to analyze the implementation of life skills education in the Negeri 1 Panjang Buya high school. This type of research is descriptive research using a qualitative approach. The research informants consisted of school principals and teachers. Data collection techniques through observation, interviews and documentation. Data analysis uses data reduction, data display, data interpretation and drawing conclusions. The results of the research show that the implementation of strengthening life skills education at the Jangka Buya 1 State High School is classified as good. The implementation of strengthening life skills-based education carried out at the Jangka Buya 1 State High School includes aspects of personal skills, academic skills, social skills and vocational skills.